Integrating the Department of Defense Supply Chain - Peltz, Eric (RAND Corporation, 2012)
The authors provide a framework for an integrated Department of Defense (DoD) supply chain, associated policy recommendations, and a companion framework for management practices that will drive people to take actions aligned with this integrated supply chain approach. Building on the framework and policy recommendations, they identify opportunities to improve DoD supply chain efficiency and highlight several already being pursued by DoD.